Implementasi Sistem Informasi Desa Berbasis NIK untuk Transformasi Layanan Administrasi dan Tanggap Bencana di Desa Mata Mamplam - Nurhayati Nurhayati; Cut Nanda Fermita; Musrizal Musrizal; Ledyana Fitriani; Ilham Ilham; Syifa Safira; Indah Maulidia; Cut Fatin Noer; Cicia Intan; Fikri Ulfa; Hafiza Hafiza (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Mata Mamplam Village faces persistent limitations in managing population administration, accessing public information, and coordinating disaster response — all of which are still handled manually, making services slow and prone to error. This community service program was designed to build and deploy a website-based Village Information System (SID) as a digital solution that addresses these specific, documented needs. The approach taken was needs-based service, involving village officials and community representatives through in-depth interviews and direct observation. The program ran through four sequential stages: needs analysis, system development, operator mentoring, and functional evaluation using black-box testing. The resulting system was built on the Next.js 14 framework with a PostgreSQL database, covering five main modules: population administration digitization based on National Identity Number (NIK) with automated PDF letter generation, public information transparency, disaster response management linked to BMKG data, a digital MSME catalog, and a no-code self-management feature. Black-box testing across all ten functional scenarios returned a 100% pass rate, and village operators demonstrated the ability to run and manage the system independently after the mentoring sessions. The deployment has measurably shifted village administrative services toward faster, more accurate, and more responsive operations.